2009
DOI: 10.1590/s1516-31802009000400006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pressure ulcers among the elderly living in long-stay institutions in São Paulo

Abstract: CONTEXT AND OBJECTIVE: The prevalence of pressure ulcers varies according to geographic region and population group, such as the institutionalized elderly. The aim of this study was to identify the prevalence of pressure ulcers among elderly people living in long-stay institutions. DESIGN AND SETTING:Cross-sectional study in six long-stay institutions for the elderly in São Paulo, Brazil. METHODS:Demographic and clinical data were collected in six long-stay institutions on two visits to each institution betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
2
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 16 publications
(38 reference statements)
2
22
2
7
Order By: Relevance
“…In our study, the age of patients with pressure ulcers was found to be statistically significantly higher than those without it. This finding is consistent with the literature, and the decrease in skin turgor along with aging and the changes in the structure of collagen increase the risk of pressure ulcer development (15,(30)(31)(32)(33)(34). However, age is not evaluated in BRDs for pressure ulcers.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, the age of patients with pressure ulcers was found to be statistically significantly higher than those without it. This finding is consistent with the literature, and the decrease in skin turgor along with aging and the changes in the structure of collagen increase the risk of pressure ulcer development (15,(30)(31)(32)(33)(34). However, age is not evaluated in BRDs for pressure ulcers.…”
Section: Discussionsupporting
confidence: 88%
“…(12,13) The material under study -transparent polyurethane film -was not applied to the sacral region, due to the fact that this region is a singular site and therefore it would be impossible to analyze it simultaneously in the same patient during the period intended for this study. The transparent polyurethane film was not applied on other skin sites mentioned in the literature as likely to develop pressure ulcer due to the fact that we did not want to expose a very large body area of the patient to the application of the material.…”
Section: Methodsmentioning
confidence: 99%
“…At this juncture, a study of prevalence of cross-sectional, conducted with 365 institutionalized elderly people in São Paulo, found that there were not significant differences in demographic and clinical characteristics of elderly patients with pressure ulcers for each month of data collection [18].…”
Section: Discussionmentioning
confidence: 95%